EDUCATION for SUSTAINABLE DEVELOPMENT (ESD) SEBUAH UPAYA MEWUJUDKAN KELESTARIAN LINGKUNGAN - Nuansa Bayu Segara (Sosio-Didaktika: Social Science Education Journal, 2015)
The end of twentieth century left the impact of life for people around the world. Changes that very large in a century that changed a manifestation of the world which was the residence and human life.The earth as if more fragile in sustains human life with all its activity. Developing countries like indonesia not separated from the condition of this difficult department. Efforts to meeting the needs of food, energy, transportation, psychology has harvested more people are a real threat. This challenge ought to be answered to the development in many sectors with the approach of sustainable. Planting sustainable value has to be introduced from the outset, one way is by introducing ESD (education for sustainable development) in schools, in the hope of school tuition having values the sustainability of it so that it be able to retain the conservation of the natural environment, social and cultural. Permalink/DOI: http://dx.doi.org/10.15408/sd.v2i1.1349